ChemInform Abstract: High‐Pressure/High‐Temperature Synthesis and Characterization of the First Palladium or Platinum Containing Lithium Transition‐Metal Sulfides Li2M3S4 (M: Pd, Pt). Issue 46 (October 2016) - Heymann, Gunter; Niehaus, Oliver; Krueger, Hannes; Selter, Philipp; Brunklaus, Gunther; Poettgen, Rainer
Abstract: The title compounds are obtained via hot pressing of stoichiometric amounts of Li3 N, Pd or Pt, and sulfur (multianvil press, 8 GPa, 1150 °C, 10 min; cooling to 500 °C within 2 h).